Essentials of Research Methodology - Charu Khurana (Essentials of Research Methodology, 2023)
Research is a logical and systematic search for new and useful information on a particular topic. Quite frequently these days people talk of research, both in academic institutions and outside. Several research studies are undertaken and accomplished year after year. But in most cases very little attention is paid to an important dimension relating to research, namely, that of research methodology. The need, therefore, is for those concerned with research to pay due attention to designing and adhering to the appropriate methodology throughout for improving the quality of research. Keeping all this in view, the present book has been written to enable health researchers, in developing the most appropriate methodology for their research studies and to make them well versed with the fundamentals of epidemiology and biostatistics. It is hoped that the humble effort made in the form of this book will assist in the accomplishment of exploratory as well as result-oriented research studies.